2019
DOI: 10.1186/s12968-019-0557-0
|View full text |Cite
|
Sign up to set email alerts
|

Loss of base-to-apex circumferential strain gradient assessed by cardiovascular magnetic resonance in Fabry disease: relationship to T1 mapping, late gadolinium enhancement and hypertrophy

Abstract: Background Cardiac involvement is common and is the leading cause of mortality in Fabry disease (FD). We explored the association between cardiovascular magnetic resonance (CMR) myocardial strain, T1 mapping, late gadolinium enhancement (LGE) and left ventricular hypertrophy (LVH) in patients with FD. Methods In this prospective study, 38 FD patients (45.0 ± 14.5 years, 37% male) and 8 healthy controls (40.1 ± 13.7 years, 63% male) underwent 3 T CMR including cine balan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 35 publications
4
37
0
3
Order By: Relevance
“…Few studies have analyzed CMR-derived GLS and GCS in AFD patients. No significant differences in GLS between AFD patients and controls have been found [ 85 ]. Regarding GCS, a significant increase in circumferential strain in patients with LVH phenotype has been found, and it may imply the presence of functional cardiovascular impairment [ 86 ].…”
Section: Tissue Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have analyzed CMR-derived GLS and GCS in AFD patients. No significant differences in GLS between AFD patients and controls have been found [ 85 ]. Regarding GCS, a significant increase in circumferential strain in patients with LVH phenotype has been found, and it may imply the presence of functional cardiovascular impairment [ 86 ].…”
Section: Tissue Characterizationmentioning
confidence: 99%
“…Regarding GCS, a significant increase in circumferential strain in patients with LVH phenotype has been found, and it may imply the presence of functional cardiovascular impairment [ 86 ]. Mathur et al demonstrated that base-to-apex CS gradient discriminates between AFD patients without hypertrophy or LGE and healthy controls independent of native T1, suggesting that loss of base-to-apex CS gradient may be an early marker of cardiac involvement in AFD [ 85 ]. More recently, Augusto et al described a slightly reduced GLS as a primary cardiac phenomenon, because of the altered myocardial coupling to the systemic vasculature due to systemic endothelial and smooth muscle changes [ 87 ].…”
Section: Tissue Characterizationmentioning
confidence: 99%
“…Based on their results with association of impairment in GLS and reduction of native T1 times without presence of LVH, the authors of a recent study suggested that mechanical dysfunction in the course of FD occurs before evidence of glycosphingolipid deposition [25]. Another study concluded that base to apex circumferential strain may be an early marker of cardiac FD involvement with independent and incremental value beyond native T1 [26].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, AFD patients show impairment in global longitudinal strain (GLS) correlated with myocardial damage degree (presence of LGE and cardiac biomarkers) and nT1 values, even at pre-hypertrophic stage [38]. Furthermore, AFD is characterized by reduction in global circumferential strain (GCS) and in GCS gradient from the LV base to the apex [39].…”
Section: Lysosomal Storage Diseasementioning
confidence: 99%